Incorporación del Tribunal Federal de Justicia Fiscal y Administrativa al Poder Judicial de la Federación - Vázquez Bustos, Vicente (Acta Universitaria, 2003)
The Fiscal Court of the Federation, today Federal Court of Fiscal and Administrative Justice, arises within the Law of Fiscal Justice with vicarial jurisdiction, solving on behalf of the President thru the empowerment that the Law bestows in it, with strong roots in the French administrative right and from the beginning with exclusive jurisdiction on fiscal matters. The evolution and transformation experienced by the Federal Court of Fiscal and Administrative Justice, motivate a deep and profound reflection on its legal nature and the issuing resolutions (among other aspects) around the continuous reforms to its own Organic Law, as well as to diverse laws, that have provided it with a permanent new jurisdiction. The idea is to strengthen the Body of Fiscal Justice, analyzing the convenience, the means and the consequences of incorporating it to the Judicial Power of the Federation.
Keywords: Array; Array; Array